Hubungan Pemerintahan antara Pemerintah Pusat dan Pemerintah Daerah Serta Peran Wakil Pemerintah - NURCHOLIS, HANIF (Universitas Muhammadiyah Yogyakarta, 2011)
The local government is part of a national government empowered to regulate and administergovernmental affairs entrusted to her. Therefore, between central and local governments have asystemic relationship between sub-systems so as to form an integral system of government. Therelationship between central and local governments is determined in its oversight system that rests ontwo bases: hierarchical and functional. Base hierarchy to determine the extent to which higherauthority overseeing the local government while the functional basis to determine the extent to whichfunctional departments / sectoral and local government departments overseeing general. Based on thissurveillance pattern then there are four models of relationships referred to by the countries in thisworld with many variants. Four models are models of French, British model, German model, andmodel of the Soviet Union. Indonesia's New Order embraced the French model, while at theReformation Orde more embracing German model